Recurrent Miscarriages in Advance Maternal Age (>35 Years) - Munir, Ayesha; Qureshi, Asim Iqbal; Rasheed, Tahreem; Shafi, Shazia; Gul, Pari Iman; Tahir, Umber Arooj (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine frequency of recurrent miscarriages in advance maternal age (>35 years). Study Desing: Descriptive cross-sectional study. Place and Duration of the Study: Department of Obstetrics and Gynaecology, Bakhtawar Amin Trust Teaching Hospital, Multan, Pakistan, from January 2021 to June 2021. Material and Methods: One hundard and ninty six women were enrolled. The demographic information like name, age, address, number of gravida, para and the number of miscarriages was obtained. The outcome variable (proportion of woman having recurrent miscarriages) was recorded on a specific proforma. Descriptive statistics were applied to analyze the data. Results: Among 196 women, 122 (62.2%) were aged between 35 to 40 years. Overall mean age was calculated to be 38.1+3.6 years. Analysis of gravidity and parity distribution showed that majority of women, 55 (28.1%) were G6P1A4 while G5P1A3 were 41 (20.9%). There were 86 (43.9%) women who had conceived 6 times in the past. Among 196 women with recurrent miscarriages, majority of the patients 109 (55.6%) were having previous 3 miscarriages. Frequency of recurrent miscarriages in maternal age >35 years in the present study was found to be 14.8% Conclusion: Increased risk of fetal loss was observed with increasing maternal age in women aged more than 35 years. Frequency of recurrent miscarriages in advance maternal age was 14.8%.